2019
DOI: 10.3389/fnins.2019.00861
|View full text |Cite
|
Sign up to set email alerts
|

Pre-plaque Aß-Mediated Impairment of Synaptic Depotentiation in a Transgenic Rat Model of Alzheimer’s Disease Amyloidosis

Abstract: How endogenously produced soluble amyloid ß-protein (Aß) affects synaptic plasticity in vulnerable circuits should provide insight into early Alzheimer’s disease pathophysiology. McGill-R-Thy1-APP transgenic rats, modeling Alzheimer’s disease amyloidosis, exhibit an age-dependent soluble Aß-mediated impairment of the induction of long-term potentiation (LTP) by 200 Hz conditioning stimulation at apical CA3-to-CA1 synapses. Here, we investigated if synaptic weakening at these synapses in the form of activity-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 56 publications
2
6
0
Order By: Relevance
“…To investigate any potential beneficial effects of light and sound stimulation synchronized at 40 Hz we studied pre-plaque transgenic animals first (Figure 1A,B). Consistent with our previous reports (Qi et al, 2014;Qi et al, 2019), whereas 200 Hz HFS induced robust synaptic LTP in the hippocampus of wild-type rats (Untreated WT, p=0.0059, compared with pre-HFS baseline), LTP was only transient in age-matched pre-plaque APP transgenic rats, being completely blocked at 3 h post-HFS (Untreated TG, p=0.1775, compared with pre-HFS baseline and p=0.0167, compared with Untreated WT). A two-week treatment consisting of two-hour daily sessions completely abrogated the LTP deficit in transgenic rats (40 Hz TG, p=0.0071, compared with pre-HFS baseline and p>0.9999, compared with Untreated WT, p=0.0009, compared with Untreated TG, Figure 1B).…”
Section: Resultssupporting
confidence: 91%
“…To investigate any potential beneficial effects of light and sound stimulation synchronized at 40 Hz we studied pre-plaque transgenic animals first (Figure 1A,B). Consistent with our previous reports (Qi et al, 2014;Qi et al, 2019), whereas 200 Hz HFS induced robust synaptic LTP in the hippocampus of wild-type rats (Untreated WT, p=0.0059, compared with pre-HFS baseline), LTP was only transient in age-matched pre-plaque APP transgenic rats, being completely blocked at 3 h post-HFS (Untreated TG, p=0.1775, compared with pre-HFS baseline and p=0.0167, compared with Untreated WT). A two-week treatment consisting of two-hour daily sessions completely abrogated the LTP deficit in transgenic rats (40 Hz TG, p=0.0071, compared with pre-HFS baseline and p>0.9999, compared with Untreated WT, p=0.0009, compared with Untreated TG, Figure 1B).…”
Section: Resultssupporting
confidence: 91%
“…This finding is consistent with previous studies on the acute action of CORT on LTP induced using generally milder conditioning protocols [ 13 , 43 ]. The latter protocols induce NMDA receptor-dependent LTP whereas sHFS-induced LTP is also voltage-gated Ca 2+ channel-dependent [ 26 , 28 ]. Here, short-term CORT acutely impaired a relatively late (3 h) phase of LTP while an earlier phase of LTP (<1 h) appeared unscathed.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive function is impaired before the formation of plaques, as early as 3 months of age [ 25 ]. We chose to inject animals at an age (4–5 month) when LTP is impaired by the build-up of Aß oligomers but prior to the deposition of plaques [ 26 , 27 ]. All experiments were carried out in accordance with the approval of the Health Products Regulatory Authority, Ireland, using methods similar to those described previously [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, Kim et al [31] demonstrated that the Aß-containing C-terminus of ß-APP (CT; the product of β-secretase cleavage of APP) reversed LTP when applied 10 min after LTP induction, while Huh et al [26] showed that DP could not be induced in slices from aged Tg2576, a transgenic mouse model harboring the APP 695 SWE mutation. A very recent in vivo study by Qi et al [57] reported that 4–6-month-old, anaesthetized, pre-plaque TG (McGill-R-Thy1-APP) rats developed only a transient DP at apical synapsed in the CA1 region upon LFS at 1 Hz, while the same stimulation caused complete LTP reversal in WT animals. Interestingly, DP could be rescued by application of an antibody that specifically binds Aß oligomers.…”
Section: Discussionmentioning
confidence: 99%